Improving Students' Speaking Skill Through Discussion In Grade XI Of SMA Muhammadiyah 5 Jaten 2012/2013 Academic Year - Muflikhah, Linna Marngatun, Agus Wijayanto, Ph. D., Nur Hidayat S. Pd (2013)
The objectives of this research are to describe whether or not teaching speaking by using discussion method can increase students' speaking skill and o identify the difficulties faced by the students in using discussion as method to increase their speaking skill in grade XI of SMA M 5 Jaten.In achieving the objectives of this research, the researcher uses collaborative research. Each cycle of this research consists of four steps: planning, implementing, observing, and reflecting. The subjects of this research consist of 26 students. In analyzing the data the researcher uses both qualitative and quantitative analysis. Qualitative analysis was done based the process of teaching and learning process. While quantitative analysis was done based to the scores of pre-test and post-test. There were three cycles in this research, each cycle conducted in two meetings. The result of the research shows that the average score of pre-test is 37.6, post-test one is 5.6, post-test two is 2 53, post-test three is 3 66.15 and final test is 63. Those scores indicate that the students have an improvement in speaking ability. Through discussion the students become more confident and more critical. Then, it can be called that teaching speaking through discussion is succesful to improve students speaking ability in SMA M 5 Jaten. There were some weaknesses of discussion; (1) just problematic materials could be used, (2) some of them depend on with clever students, (3) many students may dominated the discussion, (4) subjective scoring, (5) moves slowly the class, and (6) takes long time.